SUITABILITY OF GDRP IN THE TOURISM SECTOR WITH THE SPATIAL PLANNING OF WEST PESISIR REGENCY - Rasman, Afifah (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2025)
West Pesisir Regency is one of the areas with great potential for developing the tourism sector, including the marine tourism sector, especially beaches. West Pesisir Regency has a tourism sector that is quite promising to be developed, as evidenced by the large number of tourists visiting West Pesisir Regency, both local and foreign tourists, namely in 2017 there were 135,833 tourists, but in 2020 there were 50,730 tourists and in 2021 it decreased by 97% to 1,128 due to the COVID 19 pandemic. Spatial planning for West Pesisir Regency aims to realize West Pesisir Regency as a tourism destination based on agricultural and marine industries that pay attention to aspects of local wisdom and environmental sustainability. The West Pesisir Regency Government, based on its spatial planning objectives, is trying to pay more attention to tourism development because the tourism sector has an important role in shaping the size of the GRDP, namely distribution of 3.09% and the GRDP growth rate reaching 35.09 in 2019. However, after the pandemic COVID 19, the distribution of GRDP in the tourism sector became 2.76% and the growth rate of GRDP in the tourism sector decreased to -4.41 in 2021. Therefore, this research aims to determine the suitability of GRDP in the tourism sector with the spatial planning of West Pesisir Regency. This research was conducted in West Pesisir Regency using secondary data, namely GRDP data originating from the BPS- Statistics and document review. This research uses LQ, SS, and Klassen Typology analysis methods. The results of this research indicate that the GRDP of the tourism sector is following the spatial planning objectives of West Pesisir Regency because it is a base sector, progressive, superior, developed, and fast-growing sector.